Morphology controlling of 〈111〉-3C–SiC films by HMDS flow rate in LCVD. Issue 5 (18th January 2019) - Xu, Qingfang; Tu, Rong; Sun, Qingyun; Yang, Meijun; Li, Qizhong; Zhang, Song; Zhang, Lianmeng; Goto, Takashi; Ohmori, Hitoshi; Shi, Ji; Li, Haiwen; Kosinova, Marina; et al.
Abstract : Morphology of 〈111〉-oriented 3C–SiC films was transformed from mosaic to whisker to cauliflower-like with the increased flow rate ( f ) of hexametyldisilane (HMDS) in the process of laser chemical vapor deposition (LCVD). Abstract : Morphology of 〈111〉-oriented 3C–SiC films was transformed from mosaic to whisker to cauliflower-like with the increased flow rate ( f ) of hexametyldisilane (HMDS) in the process of laser chemical vapor deposition (LCVD). The SiC whiskers were naturally sharp hexagonal pyramids with average height of 250 nm and an aspect ratio in the range of 5 to 10, with a density of 1.3 × 10 8 mm −2 . The influence mechanism of f on the surface morphology, as well as the growth mechanism of SiC whiskers, was discussed.